2015
DOI: 10.2174/1381612822666151109111712
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution Exposure and Blood Pressure: An Updated Review of the Literature

Abstract: Both high arterial blood pressure (BP) and elevated levels of fine particulate matter (PM2.5) air pollution have been associated with an increased risk for several cardiovascular (CV) diseases, including stroke, heart failure, and myocardial infarction. Given that PM2.5 and high BP are each independently leading risk factors for premature mortality worldwide, a potential relationship between these factors would have tremendous public health repercussions. Therefore, the aim of this review is to summarize recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
157
2
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(172 citation statements)
references
References 0 publications
9
157
2
4
Order By: Relevance
“…ED visits for heart failure appeared first at lag 0 and increased with time, with the highest RR at lag 3. In contrast to the mechanisms accounting for the triggering of myocardial infarction, hospitalizations for heart failure are most likely secondary to exacerbations of pre‐existing heart failure worsened by PM‐induced increases in systemic blood pressure, and systemic and pulmonary vasoconstriction 38, 39, 40, 41. All these outcomes were most strongly associated with the aged.…”
Section: Discussionmentioning
confidence: 99%
“…ED visits for heart failure appeared first at lag 0 and increased with time, with the highest RR at lag 3. In contrast to the mechanisms accounting for the triggering of myocardial infarction, hospitalizations for heart failure are most likely secondary to exacerbations of pre‐existing heart failure worsened by PM‐induced increases in systemic blood pressure, and systemic and pulmonary vasoconstriction 38, 39, 40, 41. All these outcomes were most strongly associated with the aged.…”
Section: Discussionmentioning
confidence: 99%
“…A priori selected covariates were extracted from medical records: age at childbirth (continuous), race/ethnicity (white, black, Hispanic, Asian/Pacific Islander, other/unknown), marital status (married, unmarried, missing/unknown), insurance (private, public, self-pay/other), parity (nulliparous, multiparous), prepregnancy body mass index (calculated as weight (kg)/ height (m) 2 ; <18.5, 18.5-24.9, 25.0-29.9, ≥30.0, or unknown), preexisting chronic disease (any (diabetes mellitus, asthma, thyroid disease, or human immunodeficiency virus), none), smoking during pregnancy (yes, no), alcohol consumption during pregnancy (yes, no), and season of conception (spring, summer, fall, winter). Analyses were also adjusted for study site to account for both measured and unmeasured area-level indicators, including but not limited to socioeconomic status, case ascertainment, and sources of air pollution exposures.…”
Section: Covariatesmentioning
confidence: 99%
“…Emerging data have linked air pollution to hypertensive disorders (2). In particular, pregnancy is characterized by profound hemodynamic changes in response to the needs of the developing fetus (3).…”
mentioning
confidence: 99%
“…Due to its potential threat to human health and the environment, PM 2.5 has been given high priority in research activities in the fields of air pollution and environmental health [2][3][4]. Recent epidemiological studies have shown an association between PM 2.5 and adverse effects on human health, including an increased risk of cardiovascular diseases [5,6], heart problems and lung cancer [7], and a significantly reduced birth rate [8,9]. PM 2.5 pollution has become one of the critical air problems and seriously affects people's daily lives worldwide.…”
Section: Introductionmentioning
confidence: 99%